1994
DOI: 10.1111/j.1755-3768.1994.tb02805.x
|View full text |Cite
|
Sign up to set email alerts
|

Uveitis survey at the University Eye Clinic in Turku

Abstract: We conducted a retrospective analysis of 1122 patients with endogenous uveitis treated at the University Eye Clinic in Turku during the years 1980-1982 and 1988. Of the 1122 patients 568 were men and 554 women; 1034 (92.2%) had anterior uveitis, 15 (1.3%) intermediate uveitis, 64 (5.7%) posterior uveitis and 9(0.8%) panuveitis; 867 (77.3%) were unilateral and 255 bilateral; 789 of 1067 cases (73.9%) were of sudden onset and 278 of insidious onset; 808 of 1102 cases (73.3%) were of short duration and 294 of lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…Our percentage for sarcoidosis (2%) was similar to that reported in previous studies 14,21 but lower than that found in others. 15,22 HLA B27-positive acute anterior uveitis accounted for only 10% of all cases in our study.…”
Section: Discussionsupporting
confidence: 88%
“…Our percentage for sarcoidosis (2%) was similar to that reported in previous studies 14,21 but lower than that found in others. 15,22 HLA B27-positive acute anterior uveitis accounted for only 10% of all cases in our study.…”
Section: Discussionsupporting
confidence: 88%
“…The relative frequencies of anatomical classifications are comparable to data published in other Middle European series from tertiary care centers but differ from the data of other Northern European countries, where up to 96% of the cases were reported to have anterior uveitis [30-35]. In the posterior and panuveitis groups, the rate of unclassified cases was the lowest at around 20%, and in the posterior uveitis group the frequency of toxoplasmosis was even higher than that among unclassified cases.…”
Section: Discussionsupporting
confidence: 65%
“…However, new cases of tuberculous uveitis did not appear after the year 1981, which reflects the decrease of the incidence of systemic tuberculosis during past decades. In this study there was not a single case of syph Similar disappearance of tuberculosis and syphilis as conspicuous causes of uveitis could be seen both in Finland (Miettinen 1958;Saari et al 1975;Paivonsalo-Hietanen et al 1994) and in the United States (Woods 1960;Perkins & Folk 1984;Henderly et al 1987).…”
Section: Discussionmentioning
confidence: 52%
“…Toxoplasmic retinochoroiditis was the leading cause of posterior uveitis, accounting for 20-54% of these cases both in Europe (Saari et al 1975;Perkins & Folk 1984;Vadot et al 1984;Paivonsalo-Hietanen et al 1994) and in the United States (Perkins & Folk 1984;Henderly et al 1987;Holland & Engstrom 1988) and it was the leading cause of all uveitis cases in Nigeria (Ayanru 1977) and in Brazil (Belfort 1988). The incidence of toxoplasmic retinochoroiditis was 0.3 per 100 000 population in this study and 2.16 per 100 000 population in France (Vadot et al 1984).…”
Section: Discussionmentioning
confidence: 99%